A method for surface modification of GH4169 material by ion implantation

The surface modification of the GH4169 material through ion implantation technology is carried out to form a controllable injection layer, which solves the problem of material being easily worn and failed under extreme operating conditions, significantly improves friction and wear resistance and extends the service life of parts.

CN119776790APending Publication Date: 2025-04-08BEIJING RES INST OF AUTOMATION FOR MACHINERY IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510058355.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

GH4169 materials are prone to wear and fail in extreme working conditions, resulting in shortening the service life of parts. The existing thermal spraying technology has hidden dangers of peeling and low yield.

Method used

The surface modification of GH4169 material is carried out by ion implantation technology, and a controllable implantation layer is formed through non-metal ions and metal ions implantation, improving the material's friction and wear resistance.

Benefits of technology

It significantly improves the friction and wear resistance of GH4169 material, extends the service life of parts, and avoids peeling problems in thermal spraying technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776790A_ABST
    Figure CN119776790A_ABST
Patent Text Reader

Abstract

The present invention discloses a method for surface modification of GH4169 material by ion implantation, comprising the following steps: performing surface polishing and cleaning on the GH4169 material; placing the GH4169 material in a vacuum chamber of an ion implantation device for vacuuming; heating the GH4169 material; performing non-metallic ion implantation and metal ion implantation on the GH4169 material 3-5 times in sequence; wherein the non-metallic ion implantation dosage is controlled to be 1×10 17 ‑10×10 17 ions / cm 2 The non-metal ion implantation depth is 250-380nm; the metal ion implantation dose is controlled to be 1×10 17 ‑5×10 17 ions / cm 2 , the metal ion implantation depth is 110-150nm; the present invention can effectively improve the friction and wear resistance of parts, solve the problem of easy wear and failure of GH4169 material parts under extreme working conditions, and extend the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of surface modification of metal materials, and in particular to a method for surface modification of GH4169 material by ion implantation. Background Art

[0002] GH4169 material is a nickel-based high-temperature alloy with excellent mechanical properties, good corrosion resistance and processing performance. It is one of the commonly used metal materials in aerospace and is often used in key parts of aircraft and rocket engines. With the continuous development of aviation and aerospace technology, higher requirements are also put forward for the performance of parts used under special working conditions. GH4169 materials are prone to wear and failure under extreme working conditions such as high temperature, ultra-low temperature, high speed, and heavy load, which seriously affects the service life of parts. Therefore, it is necessary to carry out wear-resistant treatment of GH4169 materials to improve the service life of parts.

[0003] At present, thermal spraying technology is commonly used in China to prepare chromium oxide wear-resistant coating on the surface of parts to improve the wear resistance of parts. However, thermal spraying technology has some disadvantages. Its hard wear-resistant coating is thicker and has a larger surface roughness. The surface still needs secondary processing, and the yield rate is low. In addition, the coating has the risk of peeling off under ultra-low temperature conditions. The peeled hard coating particles will not only cause abrasive wear of the workpiece and accelerate its failure, but also flow into the interior of the parts, causing fatal risks.

[0004] Therefore, under the premise of requiring the accuracy and size of components to remain unchanged, a better technology is urgently needed to improve the wear resistance of GH4169 material. Summary of the invention

[0005] In view of the above technical problems, the purpose of the present invention is to provide a method for ion implantation surface modification of GH4169 material, which can greatly improve the friction and wear resistance of GH4169 material parts, solve the problem of easy wear and failure of GH4169 material parts under extreme working conditions, and extend the service life.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for surface modification of GH4169 material by ion implantation, comprising the following steps:

[0008] S100, surface polishing and cleaning of GH4169 material;

[0009] S200, placing the cleaned GH4169 material into a vacuum chamber of an ion implantation device, evacuating the chamber, and heating the GH4169 material to 50-600° C.;

[0010] S300, non-metallic ion implantation is performed on the GH4169 material using a gas ion source, and the non-metallic ion implantation dose is controlled to be 1×10 17 -10×10 17 ions / cm 2 , the non-metal ion implantation depth is 250-380nm;

[0011] S400, using MEVVA ion source to perform metal ion implantation on the GH4169 material, controlling the metal ion implantation dose to be 1×10 17 -5×10 17 ions / cm 2 , the metal ion implantation depth is 110-150nm;

[0012] The steps S300 and S400 are cycled 3-5 times in sequence.

[0013] Specifically, the step S100 includes:

[0014] S101, polishing: polishing the surface of the GH4169 material with a sander.

[0015] S102, chemical ultrasonic cleaning: first use a metal degreasing solvent to remove grease on the surface of the GH4169 material, soak it in tetrachloroethylene for 15-30 minutes, and ultrasonically clean it; then use a metal rust remover to clean the rust spots on the surface of the GH4169 material, soak it in acetone for 15-30 minutes, and ultrasonically clean it; finally, soak the GH4169 material in alcohol for 15-30 minutes, and ultrasonically clean it; wipe it dry with a clean silk cloth, place it in a vacuum oven to dry for 2-4 hours, and then take it out.

[0016] Specifically, in step S200, the vacuum chamber is evacuated to a vacuum degree of 1×10 -3 -3×10 -3 Pa.

[0017] Specifically, in step S300, high-purity gas is introduced into the vacuum chamber, the gas ion source is nitrogen or oxygen with a purity of 99.99%, the gas flow rate is controlled to be 10-100 sccm, and the gas pressure in the vacuum chamber is maintained at 1×10 -3 -5×10 -3 pa;

[0018] Specifically, in step S300, each time non-metallic ions are injected, the filament power supply and the grid voltage are turned on, the acceleration voltage is adjusted to 50-100 kV, the acceleration current is adjusted to 1-10 mA, the suppression voltage is adjusted to 0.5-5 KV, and the suppression current is adjusted to 0-10 mA.

[0019] Specifically, in step S400, the injected ions are one of zirconium ions, titanium ions, chromium ions or molybdenum ions; the metal source of the metal ions is a metal target material with a purity of more than 99.9%;

[0020] Specifically, in the step S400, each time metal ions are injected, the suppression voltage is controlled to be 0.1-10 kV, the suppression current is controlled to be 0-15 mA, the extraction voltage is controlled to be 30-100 kV, and the extraction current is controlled to be 1-20 mA.

[0021] Specifically, the friction coefficient of the surface of the GH4169 material after ion implantation surface modification is less than 0.45.

[0022] Specifically, the microhardness of the surface of the GH4169 material modified by ion implantation changes within 10%, and the nanohardness increases by 10-50%.

[0023] The beneficial effects of the present invention are as follows:

[0024] The method for surface modification of GH4169 material by ion implantation of the present invention comprises the following steps: placing the GH4169 material in a vacuum chamber of an ion implantation device for evacuation, heating the GH4169 material, and then cyclically implanting non-metallic ions and metal ions into the GH4169 material for 3 to 5 times; wherein the non-metallic ion implantation dosage is controlled to be 1×10 17 -10×10 17 ions / cm 2 The non-metal ion implantation depth is 250-380nm; the metal ion implantation dose is controlled to be 1×10 17 -5×10 17 ions / cm 2 The metal ion implantation depth is 110-150nm; the present invention can significantly improve the friction and wear resistance of the GH4169 material by designing a controllable ion implantation layer process for the GH4169 material, solve the technical problem that the GH4169 material parts are prone to wear and failure under extreme working conditions, improve the friction and wear resistance of the parts, and extend the service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a photo of the wear scar surface morphology after the friction test of the GH4169 material without ion implantation surface modification;

[0026] Figure 2 This is a photo of the wear scar surface morphology of the GH4169 surface modified material obtained in Example 1 after the friction test;

[0027] Figure 3Schematic diagram of wear scar width and depth after friction test of GH4169 material without ion implantation surface modification;

[0028] Figure 4 Schematic diagram of the wear scar width and depth of the GH4169 surface modified material obtained in Example 1 after friction testing. DETAILED DESCRIPTION

[0029] In order to better explain the present invention, the present invention is described in detail with reference to the embodiments of the present invention, and the main contents of the present invention are further illustrated in conjunction with specific examples, but the content of the present invention is not limited to the following examples. If no specific technology or conditions are indicated in the examples, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0030] Compared with thermal spraying chromium oxide coating technology, ion implantation technology has the following advantages: (1) Almost any element can be implanted; (2) New alloy phases can be obtained, which can effectively change the surface properties of the material; (3) Good uniformity and repeatability; (4) The most important point is that it is firmly bonded to the substrate and there is no peeling problem. This is very important for improving the life of the component sleeve and working reliability; (5) It will not change the size of the workpiece and can be used as the last processing step of the component.

[0031] The present invention adopts ion implantation technology to perform surface modification on GH4169 material, and can significantly improve the friction and wear resistance of GH4169 material by designing a controllable ion implantation layer process for GH4169 material; the method for surface modification of GH4169 material by ion implantation of the present invention comprises heating the GH4169 material, and then cyclically implanting non-metallic ions and metal ions for 3-5 times; wherein the non-metallic ion implantation dosage for each time is controlled to be 1×10 17 -10×10 17 ions / cm 2 The non-metal ion implantation depth is 250-380nm; the metal ion implantation dose is controlled to be 1×10 17 -5×10 17 ions / cm 2 , the metal ion implantation depth is 110-150nm.

[0032] The present invention is further described in detail below through examples and related performance tests.

[0033] Example 1: Surface modification of GH4169 material by ion implantation

[0034] The specific steps include:

[0035] S100, pre-treat the GH4169 material: polish the surface of the GH4169 material with a sander, and then perform chemical ultrasonic cleaning on the GH4169 material: first use a metal degreasing solvent to remove the grease on the surface of the GH4169 sample, soak it in tetrachloroethylene for 30 minutes, and ultrasonically clean it; then use a metal rust remover to clean the rust spots on the surface of the GH4169 sample, soak it in acetone for 30 minutes, and ultrasonically clean it; finally, soak the GH4169 sample in alcohol for 30 minutes, and ultrasonically clean it. Wipe it dry with a clean silk cloth, place it in a vacuum oven and dry it for 2 hours before taking it out;

[0036] S200, put the cleaned GH4169 material into the fixture in the vacuum chamber of the ion implantation equipment and fix it, and evacuate it to 1×10 -3 Pa, heating the GH4169 material to 500° C.;

[0037] S300, using a gas ion source to perform non-metal ion implantation on the GH4169 material;

[0038] S400, using a MEVVA ion source to perform metal ion implantation on the GH4169 material.

[0039] Among them, steps S300 and S400 are non-metallic ion implantation step and metal ion implantation step respectively, and S300 and S400 are alternately cycled for 3 times. After the ion implantation process is completed, the power is turned off, and the GH4169 surface modification material is taken out after the vacuum chamber is cooled.

[0040] First non-metallic ion implantation: The gas ion source is nitrogen with a purity of 99.99%, the gas flow rate is 50 sccm, and the gas pressure in the vacuum chamber is maintained at 1×10 -3 pa, the accelerating voltage is 80 kV, the accelerating current is 9 mA, the suppressing voltage is 5 kV, the suppressing current is 8 mA, and the non-metallic ion implantation dose is 3 × 10 17 ions / cm 2 .

[0041] The first metal ion implantation: the metal ions implanted are titanium ions, the suppression voltage is 8KV, the suppression current is 12mA, the extraction voltage is 50kV, the extraction current is 10mA, and the metal ion implantation dose is 4×10 17 ions / cm 2 .

[0042] Second non-metallic ion implantation: The gas ion source is nitrogen with a purity of 99.99%, the gas flow rate is 50 sccm, and the gas pressure in the vacuum chamber is maintained at 1×10 -3pa, the accelerating voltage is 65 kV, the accelerating current is 8 mA, the suppressing voltage is 4 kV, the suppressing current is 6 mA, and the non-metallic ion implantation dose is 2.5 × 10 17 ions / cm 2 .

[0043] Second metal ion implantation: The metal ions implanted are titanium ions, the suppression voltage is 6KV, the suppression current is 10mA, the extraction voltage is 40kV, the extraction current is 8mA, and the metal ion implantation dose is 3.5×10 17 ions / cm 2 .

[0044] The third non-metallic ion implantation: The gas ion source is nitrogen with a purity of 99.99%, the gas flow rate is 50 sccm, and the gas pressure in the vacuum chamber is maintained at 1×10 -3 pa, the accelerating voltage is 65 kV, the accelerating current is 8 mA, the suppressing voltage is 4 kV, the suppressing current is 6 mA, and the non-metallic ion implantation dose is 2.5 × 10 17 ions / cm 2 .

[0045] The third metal ion implantation: the metal ions implanted are titanium ions, the suppression voltage is 6KV, the suppression current is 10mA, the extraction voltage is 40kV, the extraction current is 8mA, and the metal ion implantation dose is 3.5×10 17 ions / cm 2 .

[0046] After the three non-metal ion implantation processes and the three metal ion implantation processes are completed, the power supply is turned off, and the GH4169 material with ion implantation surface modification is taken out after the vacuum chamber is cooled.

[0047] In Example 1, the non-metal ion implantation depth on the surface of the GH4169 material is 318 nm, and the metal ion implantation depth is 130 nm.

[0048] Comparative Example 1: Surface modification of GH4169 material by ion implantation

[0049] The specific steps include:

[0050] S100, pre-treat the GH4169 material: polish the surface of the GH4169 material with a sander, and then perform chemical ultrasonic cleaning on the GH4169 material: first use a metal degreasing solvent to remove the grease on the surface of the GH4169 sample, soak it in tetrachloroethylene for 30 minutes, and ultrasonically clean it; then use a metal rust remover to clean the rust spots on the surface of the GH4169 sample, soak it in acetone for 30 minutes, and ultrasonically clean it; finally, soak the GH4169 sample in alcohol for 30 minutes, and ultrasonically clean it. Wipe it dry with a clean silk cloth, place it in a vacuum oven and dry it for 2 hours before taking it out;

[0051] S200, put the cleaned GH4169 material into the fixture in the vacuum chamber of the ion implantation equipment and fix it, and evacuate it to a vacuum degree of 1.5×10 -3 Pa, heating the GH4169 material to 300° C.;

[0052] S300, using a gas ion source to perform non-metal ion implantation on the GH4169 material;

[0053] S400, using a MEVVA ion source to perform metal ion implantation on the GH4169 material.

[0054] Among them, S300 and S400 are alternately cycled twice in sequence. After the ion implantation process is completed, the power is turned off, and the GH4169 surface modification material is taken out after the vacuum chamber is cooled.

[0055] First non-metallic ion implantation: The gas ion source is nitrogen with a purity of 99.99%, the gas flow rate is 50 sccm, and the gas pressure in the vacuum chamber is maintained at 1×10 -3 pa, the accelerating voltage is 60 kV, the accelerating current is 7 mA, the suppressing voltage is 4 kV, the suppressing current is 6 mA, and the non-metallic ion implantation dose is 2 × 10 17 ions / cm 2 .

[0056] The first metal ion implantation: the metal ions implanted were chromium ions, the suppression voltage was 6KV, the suppression current was 8mA, the extraction voltage was 30kV, the extraction current was 3mA, and the metal ion implantation dose was 3×10 17 ions / cm 2 .

[0057] Second non-metallic ion implantation: The gas ion source is nitrogen with a purity of 99.99%, the gas flow rate is 50 sccm, and the pressure in the vacuum chamber is maintained at 1×10 -3 pa, the accelerating voltage is 50 kV, the accelerating current is 6 mA, the suppressing voltage is 3 kV, the suppressing current is 5 mA, and the non-metallic ion implantation dose is 1.5 × 10 17ions / cm 2 .

[0058] Second metal ion implantation: The metal ions implanted were chromium ions, the suppression voltage was 5 kV, the suppression current was 6 mA, the extraction voltage was 25 kV, the extraction current was 2 mA, and the metal ion implantation dose was 2.5 × 10 17 ions / cm 2 .

[0059] In Comparative Example 1, the non-metal ion implantation depth is 235 nm, and the metal ion implantation depth is 105 nm.

[0060] Comparative Example 2: Surface modification of GH4169 material by ion implantation

[0061] The specific steps include:

[0062] S100, pre-treat the GH4169 material: polish the surface of the GH4169 material with a sander, and then perform chemical ultrasonic cleaning on the GH4169 material: first use a metal degreasing solvent to remove the grease on the surface of the GH4169 sample, soak it in tetrachloroethylene for 30 minutes, and ultrasonically clean it; then use a metal rust remover to clean the rust spots on the surface of the GH4169 sample, soak it in acetone for 30 minutes, and ultrasonically clean it; finally, soak the GH4169 sample in alcohol for 30 minutes, and ultrasonically clean it. Wipe it dry with a clean silk cloth, place it in a vacuum oven and dry it for 2 hours before taking it out;

[0063] S200, put the cleaned GH4169 material into the fixture in the vacuum chamber of the ion implantation equipment and fix it, and evacuate it to a vacuum degree of 1.5×10 -3 Pa, no heating of GH4169 material;

[0064] S300, using a gas ion source to perform non-metal ion implantation on the GH4169 material;

[0065] S400, using a MEVVA ion source to perform metal ion implantation on the GH4169 material.

[0066] Wherein, steps S300 and S400 are alternately cycled twice in sequence. After the ion implantation process is completed, the power supply is turned off and the GH4169 surface modified material is taken out.

[0067] First non-metal ion: The gas ion source is nitrogen with a purity of 99.99%, the gas flow rate is 50sccm, and the gas pressure in the vacuum chamber is maintained at 1×10 -3 pa, the accelerating voltage is 60 kV, the accelerating current is 7 mA, the suppressing voltage is 4 kV, the suppressing current is 6 mA, and the non-metallic ion implantation dose is 2 × 10 17 ions / cm2 .

[0068] The first metal ion implantation: the metal ions implanted were chromium ions, the suppression voltage was 6KV, the suppression current was 8mA, the extraction voltage was 30kV, the extraction current was 3mA, and the metal ion implantation dose was 3×10 17 ions / cm 2 .

[0069] Second non-metallic ion implantation: The gas ion source is nitrogen with a purity of 99.99%, the gas flow rate is 50 sccm, and the pressure in the vacuum chamber is maintained at 1×10 -3 pa, the accelerating voltage is 50 kV, the accelerating current is 6 mA, the suppressing voltage is 3 kV, the suppressing current is 5 mA, and the non-metallic ion implantation dose is 1.5 × 10 17 ions / cm 2 .

[0070] Second metal ion implantation: The metal ions implanted were chromium ions, the suppression voltage was 5 kV, the suppression current was 6 mA, the extraction voltage was 25 kV, the extraction current was 2 mA, and the metal ion implantation dose was 2.5 × 10 17 ions / cm 2 .

[0071] In Comparative Example 2, the non-metal ion implantation depth is 195 nm, and the metal ion implantation depth is 85 nm.

[0072] <Performance Test>

[0073] 1. Microhardness test

[0074] The surface hardness of the GH4169 material without ion implantation surface modification and the GH4169 surface modified material obtained in the examples and comparative examples was tested using a HXD-1000TM / LCD digital microhardness tester. The test results are as follows.

[0075] The microhardness of the GH4169 surface modified material obtained in Example 1 is 726HK, which is 6.8% higher than that of the GH4169 substrate that has not been modified by ion implantation.

[0076] The microhardness of the GH4169 surface modified material obtained in Comparative Example 1 is 675HK, which is 4.1% higher than that of the GH4169 substrate not modified by ion implantation.

[0077] The microhardness of the GH4169 surface modified material obtained in Comparative Example 2 is 632HK, which is 2.5% higher than that of the GH4169 substrate not modified by ion implantation.

[0078] 2. Nanohardness test

[0079] The GH4169 material without ion implantation surface modification and the GH4169 surface modified material obtained in the embodiment and the comparative example were subjected to micro-Vickers hardness test using Nanotest nano-indenter, the indentation depth was one tenth of the coating thickness, each sample was tested 5 times in parallel, and the average value was taken. The test results are as follows.

[0080] The nano-hardness of the surface-modified GH4169 material obtained in Example 1 is 7.8 GPa, which is 29% higher than that of the GH4169 substrate that has not been modified by ion implantation.

[0081] The nano-hardness of the surface-modified GH4169 material obtained in Comparative Example 1 is 6.55 GPa, which is 6.1% higher than that of the GH4169 substrate that has not been modified by ion implantation.

[0082] The nano-hardness of the surface-modified GH4169 material obtained in Comparative Example 2 is 6.3 GPa, which is 3.33% higher than that of the GH4169 substrate that has not been modified by ion implantation.

[0083] 3. Wear resistance test

[0084] The wear resistance of the GH4169 material without ion implantation surface modification and the GH4169 surface modified material obtained in the embodiment and the comparative example was tested by a friction and wear tester, the grinding ball was a silicon nitride ball, the load was 50g, the friction radius was 4mm, and the test time was 30min. The experiment was repeated 3 times and the average value was taken.

[0085] The surface friction coefficient of the GH4169 surface modified material obtained in Example 1 is 0.23, and the wear resistance is improved by more than 4 times compared with the GH4169 substrate not modified by ion implantation.

[0086] The surface friction coefficient of the GH4169 surface modified material obtained in Comparative Example 1 is 0.40, and the wear resistance is improved by more than 2 times compared with the GH4169 substrate not modified by ion implantation.

[0087] The surface friction coefficient of the GH4169 surface modified material obtained in Comparative Example 2 is 0.48, and the wear resistance is improved by more than 1 times compared with the GH4169 substrate not modified by ion implantation.

[0088] Figure 1 This is a photo of the wear scar surface morphology of the GH4169 material (substrate) without ion implantation surface modification after friction testing; Figure 2 This is a photo of the wear scar surface morphology of the GH4169 surface modified material obtained in Example 1 after the friction test; Figure 3 Schematic diagram of wear scar width and depth after friction test of GH4169 material without ion implantation surface modification; Figure 4 This is a schematic diagram of the wear scar width and depth of the GH4169 surface modified material obtained in Example 1 after the friction test. Figure 1-4 It can be seen intuitively that the wear resistance of GH4169 material is significantly improved after surface modification by ion implantation.

[0089] The above results show that the method for surface modification of GH4169 material by ion implantation of the present invention adopts ion implantation technology to perform surface modification on GH4169 material, and through the process design of controllable ion implantation layer on GH4169 material, the friction and wear resistance of GH4169 material can be significantly improved, and the problem of easy wear and failure of GH4169 material parts under extreme working conditions can be solved, thereby extending its service life.

Claims

1. A method for surface modification of GH4169 material by ion implantation, characterized in that: The steps include: S100, surface polishing and cleaning of GH4169 material; S200, placing the GH4169 material into a vacuum chamber of an ion implantation device, evacuating the chamber, and heating the GH4169 material; S300, non-metallic ion implantation is performed on the GH4169 material using a gas ion source, wherein the non-metallic ion implantation dosage is 1×10 17 -10×10 17 ions / cm 2 , the non-metal ion implantation depth is 250-380nm; And S400, using MEVVA ion source to perform metal ion implantation on the GH4169 material, the metal ion implantation dose is 1×10 17 -5×10 17 ions / cm 2 , the metal ion implantation depth is 110-150nm; The steps S300 and S400 are cycled 3-5 times in sequence.

2. The method for surface modification of GH4169 material by ion implantation according to claim 1, characterized in that: The step S100 specifically includes: S101, polishing the surface of the GH4169 material with a sander; S102, removing grease from the surface of the GH4169 material with a metal degreasing solvent, soaking it in tetrachloroethylene for 15-30 minutes, and ultrasonic cleaning; S103, cleaning the rust spots on the surface of the GH4169 material with a metal rust remover, soaking it in acetone for 15-30 minutes, and ultrasonic cleaning; S104, soaking the GH4169 material in alcohol for 15-30 minutes, and ultrasonically cleaning it; wiping it dry with a clean silk cloth, and drying it in a vacuum oven for 2-4 hours, and then taking it out.

3. The method for surface modification of GH4169 material by ion implantation according to claim 1, characterized in that: In step S200, the vacuum chamber is evacuated to a vacuum degree of 1×10 -3 -3×10 -3 Pa.

4. The method for surface modification of GH4169 material by ion implantation according to claim 1, characterized in that: In the step S200, the GH4169 material is heated to 50-600°C.

5. The method for surface modification of GH4169 material by ion implantation according to claim 1, characterized in that: In the step S300, the non-metal ions are nitrogen ions or oxygen ions.

6. According to the method for surface modification of GH4169 material by ion implantation according to claim 1, in the step S300, the process of implanting non-metallic ions comprises: Introduce high-purity gas with a purity of 99.99% into the vacuum chamber, control the gas flow rate to 10-100sccm, turn on the filament power supply and grid voltage, adjust the acceleration voltage to 50-100kV, the acceleration current to 1-10mA, the suppression voltage to 0.5-5KV, the suppression current to 0-10mA, and maintain the gas pressure in the vacuum chamber at 1×10 -3 -5×10 -3 pa.

7. The method for surface modification of GH4169 material by ion implantation according to claim 1, characterized in that: In the step S400, the metal ions injected are one of zirconium ions, titanium ions, chromium ions, and molybdenum ions.

8. The method for surface modification of GH4169 material by ion implantation according to claim 1, characterized in that: In the step S400, the metal source used for the metal ion implantation is a metal target with a purity of more than 99.9%. During the metal ion implantation process, the suppression voltage is controlled to be 0.1-10KV, the suppression current is controlled to be 0-15mA, the extraction voltage is controlled to be 30-100kV, and the extraction current is controlled to be 1-20mA.

9. The method for surface modification of GH4169 material by ion implantation according to claim 1, characterized in that: The friction coefficient of the surface of the GH4169 material after ion implantation surface modification is less than 0.

45.

10. The method for surface modification of GH4169 material by ion implantation according to claim 1, characterized in that: The microhardness of the surface of the GH4169 material modified by ion implantation changes within 10%, and the nanohardness increases by 10-50%.